Characterization, sources, and atmospheric transformation of a few key short-lived climate pollutants (SLCPs) at a rural super-site in the Indo-Gangetic Plain (IGP) of India. Issue 3 (25th April 2022) - Prakash, Jai; Mishra, Harsh Raj; Mitra, Kalyan; Chandra, Bhilok; Hallquist, Mattias; Habib, Gazala; Tiwari, Geetam; Pettersson, Jan B. C.; Boman, Johan; Pleijel, Håkan; Pathak, Ravi Kant
Abstract : The observed high BC and BrC levels were linked to local biomass burning, where BrC was mostly primary in nature and co-emitted with BC. BrC transformation during the daytime was potentially associated with photochemical processes. Abstract : The Indo-Gangetic Plain (IGP) region of India faces some of the most severe air pollution problems on Earth that threaten human health, food security, ecosystems, environmental sustainability, and the climate. The aim of this study is to identify and characterize the sources of key short-lived climate pollutants (SLCPs) – black carbon (BC), brown carbon (BrC), and ozone (O3 ) – as well as other pollutants [carbon monoxide (CO) and nitrogen oxides NO X = NO and NO2 ], and interlinked atmospheric processes of their formation and transformation at our long-term air pollution monitoring station in a remote rural IGP site, the Indo-Gangetic Plains Centre for Air Research and Education (IGP-CARE). Because of its location, measurements acquired at IGP-CARE provide otherwise new information on the key SLCPs in the IGP region at a remote and rural location. The year-long measurement data at this remote site provided new insights into the variability of SLCP concentration and interlinked atmospheric processes that affect air quality in the rural IGP region. Thirteen episodic events (E1–E13) of elevated BC and BrC concentrations were identified, which can largely be attributed to the local biomass burning activities in the neighboring rural communities. It is suggested that high concentrations of BrC were mostly primary in nature and thought to be co-emitted with BC from biomass burning. Also, secondary pollutant tropospheric O3 showed elevated concentration. O3 peaks were mostly attributed to local ozone formation. Nevertheless, on several occasions, O3 emission was also attributed to regional urban areas. This study's most important finding is that BrC concentrations were relatively high throughout the year with very pronounced diurnal variation with distinct morning and evening peaks in general and a minimum at around noon time; this is hypothesized to be associated with daytime photochemical processes. Analyses using a conditional bivariate probability function (CBPF) and potential source contribution function (PSCF) suggest that regional sources likely affected the local concentrations of SLCPs. These results partly explain the high concentrations and spatial distributions of SLCPs at the local and regional scales at the IGP-CARE site in winter and autumn. In contrast, in the summer and monsoon seasons, strong convection likely favored the dilution of pollutants.